Melchior Wańkowicz and Censorship. An Analysis Based on "Ziele na kraterze" (Greens on the Crater), "Na tropach Smętka" (On Smętek’s Trail) and Excerpts from "Znowu siejemy w Polsce B" (We Sow Again in Poland B) - Nowak, Grzegorz (Porównania, 2025)
The study shows some of the methods of institutional and editorial preventive censorship during the period of the Polish People’s Republic (PRL) against selected works by Melchior Wańkowicz, published for the first time in the interwar period or in exile. A comparative analysis of the original texts of the publications shows that in the years 1958–1989, there were not only political interferences of the communist control apparatus, but also intentional actions of editorial teams in publishing houses responsible for successive editions of the books of the famous writer. The article gives the most representative examples. Full, uncensored and unre-edited editions of these books did not appear on the Polish book market until the first decade of the 21st century.